The Effect of Gradually Stirring On Halophilic Bacteria Growth with Artemia salina Nutrition for Salt Production - Nilawati Nilawati; Muryati Muryati; Marihati Marihati (Biopropal Industri, 2014)
Halophilic bacteria are microorganisms whose habitat is at high salt content. Halophilic bacteria in the presence of salt crystallization can increase the purity of NaCl. Nutrients that contain carbon and oxygen must be available for the survival of bacteria, where Artemia salina contains 52% protein and 15.49% carbohydrate. The purpose of this study was to determine the development of the growth of halophilic bacteria using nutrient Artemia salina for salt production. Three variables were used in this reserach: the first variables includes aeration and stirrer, the second variable was stirring time (½, 1, 2, 3, 4, 5 and 6 hours) and the third variable was mixing period, there were consisted of 1st, 2nd, 3rd, 4th, 5th, 6th and 7th day. The best treatment for transmitance and microbial analysis were 6 hours and seven days of aeration, each point was 33% transmitance and 2,25 x 103 colony forming unit per mililiter for microbilogy analysis.